(untitled) (Research, Society and Development, 2020)
This study was performed to review the international techniques for third molar dental age estimation applied to Brazilian adolescents. A systematic literature review was structured according to PRISMA. Six primary electronic databases were searched (PubMed, Scopus, LILACS, SciELO, Embase and Web of Science) and two sources of grey literature (Open Grey and Open Thesis) were screened. Only cross-sectional studies were included. The risk of bias was assessed with Joanna Briggs Institute tool for systematic reviews. The initial search found 2284 studies. Ten studies fulfilled the eligibility criteria. The samples varied between 288 and 2097 individuals. The sampled age interval ranged from 5 to 23 years. Seven techniques were found within the eligible studies. All the studies had low risk of bias. Three techniques: Demirjian (DEM), Nicodemo (NIC) and Cameriere (I3M) were included in the quantitative analysis. For each of the developmental stages of the techniques DEM and NIC, as well as for each measuring ratio of I3M, combined age values between studies were reported. In general, the international techniques for dental age estimation based on the radiographic assessment of the third molars were applicable to the Brazilian population.